HUBUNGAN SELF REGULATED LEARNING DAN DISIPLIN TERHADAP PRESTASI BELAJAR - Simon Alex Kristison Manurung; Lahmuddin Lubis (Analitika: Jurnal Magister Psikologi UMA, 2010)
This research aim to to know the Relation of Self Regulated Learning And Discipline of To Achievement Learn. From statistical assess the raport, achievement of students SMP Negeri I,  Lau Baleng. Subdistrict of Lau Baleng, Regency of Land; Ground Karo so lower. Seen from its percentage is class 1 ( one) that is 20%, class 2 (two) 17.7% while for the class of 3 (three) 15.5%. Generally is have low achievement to that is; class 1 ( one) reach 53.3%, class 2 (two) 51.1% and class 3 (three) 55.5%. Matter that happened effect of low achievement might possibly non having an effect on to the students, but extendedly also can have an effect on to nation future. Almost is often happened by the low achievement result the competitor educated will omit the class and very disappointing and also embarrass the their self, old fellow as well as peculiarly all teacher in SMP Negeri 1 Lau Baleng of Subdistrict of Lau Baleng, Regency of Land; Ground Karo. While extendedly is epoch on the move go forward non retreating. And epoch have never experienced of the stagnation of but having the character of dynamic. Thereby achievement influence peculiarly competitor educated by SMP Negeri 1 Lau Baleng, Subdistrict Lau throw the, Regency of Land; Ground Karo also partake to determine in order to moving forward nation in era this time, that goodness is globalization era, technologi as well as informatica.